PENENTUAN BIDANG GELINCIR POTENSI LONGSOR MENGGUNAKAN METODE GEOLISTRIK TAHANAN JENIS DI DESA SIDAMUKTI KECAMATAN PANGALENGAN KABUPATEN BANDUNG - Nada Afra Haeva, - (2020)
The location of the ground movement is in Sidamukti Village in a weak zone close to the meeting place of three different rocks. Thus, knowledge about the movement of land in this village is very necessary to reduce the risk of landslides. This paper presents the results of the slip area of a landslide potential using the Schlumberger configuration type resistivity geoelectric method. Data processing and interpretation using EarthImager 2D and RES2DINV software. The outputs of EarthImager 2D and RES2DINV are subsurface images and resistivity values. The results of data processing show that, trajectories 1-6 have the potential to have landslide slides which are suspected to be in the lahari breccia rock layers having a resistivity range of 124 Ω.m - 1316 Ω.m at depths of 1400.0 - 1424.1 m which is indicated by the presence of areas on the cross section models that have high resistivity values. The area is suspected of land movement. Keywords: Geoelectric Method, Slip surface, Schlumberger